The Relationship Between School Belonging, Peer Bullying, Teacher Support, and Academic Performance: A Multigroup Analysis by Gender - Hark Söylemez, Nesrin; Söylemez, Ömer Faruk (Psychology in the schools, 2025)
Academic performance is a complex outcome, driven by both cognitive skills and the emotional connections students form with peers, teachers, and their broader school community. The aim of this study is to examine the relationships between school belonging, peer bullying, teacher support, and academic performance, and to explore the effects of these variables on students' academic performance from a gender perspective. Seven thousand and two hundred fifty Turkish students from 196 schools participating in PISA 2022 were analyzed. Three different scales—school belonging, peer bullying, and teacher support—were developed using the PISA 2022 student survey. Structural equation modeling was used to examine the relationship between constructs and multigroup analysis was used to assess gender‐based differences. The findings indicate that school belonging, peer bullying, and teacher support have significant effects on academic performance. Additionally, peer bullying negatively affects school belonging, while teacher support positively influences school belonging and reduces peer bullying. The multigroup analysis reveals that the relationships between school belonging, peer bullying, teacher support, and academic performance differ by gender. By incorporating a gender‐based analysis, this study provides understanding of the differential impacts of school belonging, peer bullying, and teacher support on male and female students' academic outcomes. These findings offer practical guidance for developing gender‐sensitive educational interventions that support academic success and student well‐being. Female students benefit most from programs reducing peer bullying and enhancing social support, while male students show improved academic performance when their sense of school belonging is strengthened. Teacher support plays a critical role in reducing bullying and promoting school belonging, especially for male students, highlighting the need for targeted teacher training and inclusive classroom environments. Developing gender‐sensitive anti‐bullying and school belonging programs can foster safer, more supportive school climates that improve academic outcomes for all students.